2021
DOI: 10.1101/2021.06.02.21258190
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Association of Convalescent Plasma Treatment with Reduced Mortality and Improved Clinical Trajectory in Patients Hospitalized with COVID-19 in the Community Setting

Abstract: Background: Convalescent plasma (CP) quickly emerged as one of the first investigational treatment options for COVID-19. Evidence supporting CP for treating patients hospitalized with COVID-19 has been inconclusive, leading to conflicting recommendations regarding its use. The primary objective was to perform a comparative effectiveness study of CP for all-cause, in-hospital mortality in patients with COVID-19. Methods: The matched, multicenter, electronic health records-based, retrospective cohort study inc… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 25 publications
0
8
0
Order By: Relevance
“…Another PSM from the Washington DC area found a reduction in mortality with CCP use at both days 14 and 28, which reached statistical significance at the earlier date (47). Finally, a very large study from 176 community hospitals affiliated with Healthcare Corporation of America confirmed substantial mortality reduction in hospitalized patients receiving CCP within 3 days from admission (48).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Another PSM from the Washington DC area found a reduction in mortality with CCP use at both days 14 and 28, which reached statistical significance at the earlier date (47). Finally, a very large study from 176 community hospitals affiliated with Healthcare Corporation of America confirmed substantial mortality reduction in hospitalized patients receiving CCP within 3 days from admission (48).…”
Section: Resultsmentioning
confidence: 99%
“…Depending on the statistical model, the RR for 30-day mortality in high-titer CCP compared to low-titer CCP recipients ranged from 0.64 – 0.67, with an upper 95% confidence bound of 0.91 (8). Similarly, the large retrospective PSM study from Hospital Corporation of America (HCA) Healthcare-affiliated hospitals reported a 0.2% decreased risk of mortality for every 1 unit of S/Co serology level (40).…”
Section: Resultsmentioning
confidence: 99%
“…54 Unfortunately, most PSM studies did not assess this parameter at all. [55][56][57][58][59][60][61][62][63][64][65][66] 3) and provide proof of principle.…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, the PennCCP2 trial (US) 44 found a benefit in the primary clinical endpoint of disease severity and 28-day mortality, and a double-blind RCT study by O'Donnell et al, (US and Brazil) 45 found CCP was not associated with significant improvement in day 28 clinical status, but was associated with significantly improved survival. Observational studies [46][47][48][49][50][51][52][53][54] have reported mixed findings, but generally suggest that efficacy is more likely with high titer CCP in earlier and less severe disease, [46][47][48][49][50][51][52][53] or when used in those with impaired immunity. [55][56][57] Interpretation of RCT data, including those in recent metaanalyses, 58,59 is made challenging for multiple reasons: 1) the use of either untitered plasma or plasma qualified by serologic testing alone,…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, the PennCCP2 trial (US) 44 found a benefit in the primary clinical endpoint of disease severity and 28‐day mortality, and a double‐blind RCT study by O'Donnell et al, (US and Brazil) 45 found CCP was not associated with significant improvement in day 28 clinical status, but was associated with significantly improved survival. Observational studies 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 have reported mixed findings, but generally suggest that efficacy is more likely with high titer CCP in earlier and less severe disease, 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 or when used in those with impaired immunity. 55 , 56 , 57 …”
Section: Discussionmentioning
confidence: 99%